Do opportunities for low-income students at top colleges promote academic success? Evidence from Colombia's Ser Pilo Paga program - Jeffrey Penney; Steven F. Lehrer; Gloria L. Bernal; Luis Carlos Reyes (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
In 2014, the government of Colombia launched a unique meanstested and merit-based scholarship program called Ser Pilo Paga. We examine the effects of this scholarship on student performance on the country's university exit exam and other educational outcomes. Exploiting thresholds for socioeconomic status and test score performance on the high school exit exam for Ser Pilo Paga eligibility using a multi-score fuzzy regression discontinuity design, we find that the scholarship's effects on test scores to be quite limited in most cases. However, recipients of the scholarship do exhibit significant differences in enrollment, persistence, and test taking behaviour compared to non-recipients.
Keywords: I22; I23; I28; 330; Colombia; Saber Pro; scholarships; Ser Pilo Paga; test scores